Rekonstruksi Teori Nilai dalam Perspektif Ekonomi Syariah: Pendekatan Maqasid Syariah - Imam Fachruddin; Luthfi Pratama (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2024)
This study aims to reconstruct the theory of value based on the Maqashid al-Shariah approach, which refers to the five main objectives of Islamic law: the protection of religion (din), life (nafs), intellect (aql), lineage (nasl), and wealth (mal). The research employs a qualitative method with a normative-philosophical approach and a literature review of both classical and contemporary economic thought from conventional and Islamic economics. The findings reveal that the theory of value in Islamic economics is not solely determined by market mechanisms but must align with the principles of justice, public interest (maslahah), and balance as embedded in Maqashid al-Shariah. The value of an economic activity is assessed not only based on its material benefit but also on its contribution to collective well-being and the moral sustainability of society. Thus, this reconstruction of the value theory contributes to the development of a more ethical, inclusive, and purpose-driven Islamic economic system. The study recommends integrating the maqashid concept into the development of Islamic economic theory and policy in a more systematic manner.